Early Warning Systems for Banking Crisis and Sovereign Risk - Adina-Ionela STRĂCHINARU (Communications of International Proceedings, 2021)
The global financial crisis and, also, the pandemic situation, has generated the need for early warning systems, which can predict, in due time, the emergence and spread of banking crises. Macrostability deterioration can increase the country's risk. The bank crises likelihood is presented using a logistic regression, based on indicators, proposed by the European Commission. With an accuracy rate of about 89%, the results of the study captured the indicators` power to emit early signals. This is reported using the Area Under the Receiver Operating Characteristic (AUROC), recording a prediction value of approximately 91%, with a significant positive impact on the sovereign risk. As future research directions, the paper expands by capturing the correlation between sovereign risk and banking instability, with an effect on the real economy.
Keywords: AUROC; Banking Crisis; Brier Score; Early Warning Indicators; Sovereign Risk